High-toughness polyethylene composite material as well as preparation method and application thereof

By modifying shell powder and carbon nanotubes and copolymerizing with high-density polyethylene, maleic anhydride and ethylene-vinyl acetate copolymer, a high-tough polyethylene composite material was prepared, which solved the problem of insufficient impact resistance and toughness of the polyethylene composite material, and significantly improved the mechanical properties and heat resistance of the material.

CN119708675AInactive Publication Date: 2025-03-28SHENZHEN XINGBAOCHANG IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411912297.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyethylene composite materials have insufficient performance in impact resistance and toughness, limiting their application scope.

Method used

By mixing liquid paraffin and gamma-glycidyl etheroxypropyl trimethoxysilane with shell powder, epoxidized shell powder is formed, and the carbon nanotubes are amino-aminolated to form a modified filler. Then, high-density polyethylene, maleic anhydride and ethylene-vinyl acetate copolymer were copolymerized, modified fillers and lubricants were added, and kneaded through a plasticizer to prepare a high-toughness polyethylene composite material.

Benefits of technology

The tensile strength, impact strength and toughness of polyethylene composite materials are significantly improved, while enhancing their heat resistance and thermal stability, improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206003000000101
    Figure BDA0005206003000000101
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a high-toughness polyethylene composite material and a preparation method and application thereof.The composite material is obtained by mixing high-density polyethylene, modified high-density polyethylene, a modified filler, an antioxidant and a lubricant according to the mass ratio of 100: (3-7): (1-3): (0.3-0.5): (0.1-0.3), wherein the modified filler is obtained by reaction of epoxidized shell powder and aminated carbon nanotubes, the modified high-density polyethylene is obtained by reaction of high-density polyethylene, maleic anhydride and ethylene-vinyl acetate copolymer, and the composite material modified filler is chemically reacted or physically entangled with the modified high-density polyethylene and high-density polyethylene molecular chains. According to the present invention, the interface bonding force between the filler and the matrix is substantially improved, the reinforcing and toughening effects are provided in the composite material, the raw materials have excellent dispersibility and compatibility, and the material has characteristics of excellent mechanical property, high toughness, excellent heat resistance and excellent thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-toughness polyethylene composite material and a preparation method and application thereof. Background Art

[0002] Polyethylene (PE) is a widely used thermoplastic plastic that is odorless, non-toxic, has good chemical stability, can withstand most chemical corrosion, and has excellent wear resistance and low temperature resistance. It is widely used in packaging materials, building materials, wires and cables, agricultural films, medical devices, etc. However, polyethylene itself is a brittle material with relatively low impact resistance and toughness, which limits the scope of polyethylene's application.

[0003] The composite material obtained by filling inorganic particles in the polyethylene resin matrix often has great improvements in strengthening, toughening, heat resistance, etc. Chinese patent application CN110452437A discloses a polyethylene film with high mechanical strength and good wear resistance and a preparation method thereof, wherein the raw materials include PE, polyisobutylene, shell powder, nano calcium carbonate, graphene, phytic acid, octaphenyl cage-shaped silsesquioxane, coupling agent, processing aid, composite antibacterial agent and antioxidant, montmorillonite, and toughening agent, and the prepared polyethylene film has good processing performance, simple process, low cost reduction, and good mechanical properties, but the dispersibility between the raw materials is poor, the compatibility is poor, and the toughness is general, which affects the comprehensive performance of the polyethylene film. Chinese patent application CN102002191A discloses a high-toughness and high-strength polyethylene composite material and a preparation method thereof, wherein the composite material includes polyethylene, phenolic resin, curing agent, compatibilizer, toughening agent, antioxidant, lubricant, and phenolic resin, and the heat resistance of the composite material is improved, but the mechanical strength is general, and the tensile and impact strength are not greatly improved.

[0004] Therefore, it is of great practical significance to develop a high-strength polyethylene composite material to improve the comprehensive performance of the material. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a high-toughness polyethylene composite material and a preparation method and application thereof, which solves the problem of poor impact resistance of polyethylene and improves the mechanical properties of polyethylene.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the present invention discloses a method for preparing a high-toughness polyethylene composite material, comprising the following steps:

[0009] Step (1), mixing liquid paraffin and γ-glycidyloxypropyltrimethoxysilane evenly, adding shell powder, heating and stirring, reacting, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 hours, and grinding evenly to obtain epoxidized shell powder;

[0010] Step (2), ultrasonically dispersing the carbon nanotubes into deionized water, adding γ-aminopropyltriethoxysilane after the dispersion is uniform, stirring and mixing, reacting, centrifuging after the reaction is completed, washing with anhydrous ethanol, and drying at 80° C. for 24 h to obtain amino carbon nanotubes;

[0011] Step (3), mixing butyl acetate, epoxidized shell powder and amino carbon nanotubes, heating and reacting in a nitrogen atmosphere, and after the reaction, rotary evaporating and drying at 80° C. for 12 h to obtain a modified filler;

[0012] Step (4), uniformly mixing high-density polyethylene (HDPE), maleic anhydride, ethylene-vinyl acetate copolymer (EVA) and an initiator, and mixing them in a Hake mixer to obtain a modified high-density polyethylene;

[0013] Step (5), uniformly mixing high-density polyethylene, modified high-density polyethylene, modified filler, antioxidant, and lubricant, kneading in a double-roll open plastic mill, and discharging to obtain a high-toughness polyethylene composite material.

[0014] Preferably, in step (1), the mass ratio of liquid paraffin, γ-glycidyloxypropyltrimethoxysilane and shell powder is 1500-1800:35-50:100.

[0015] Preferably, the reaction temperature in step (1) is 105-115° C., and the reaction time is 1-2 h.

[0016] Preferably, the carbon nanotubes in step (2) are hydroxylated multi-walled carbon nanotubes.

[0017] Preferably, in step (2), the mass ratio of carbon nanotubes, deionized water and γ-aminopropyltriethoxysilane is 100:4800-5500:42-60.

[0018] Preferably, the reaction temperature in step (2) is 25-35° C., and the reaction time is 24-30 h.

[0019] Preferably, in step (3), the mass ratio of butyl acetate, epoxidized shell powder and amino carbon nanotubes is 2500-3500:100:85-120.

[0020] Preferably, the reaction temperature in step (3) is 80-95° C., and the reaction time is 5-8 h.

[0021] Preferably, in step (4), the mass ratio of high-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator is 100:1-2:5-20:0.1-0.2.

[0022] Preferably, during the banburying process in step (4), the rotation speed is 40-60 r / min, the banburying temperature is 160-180° C., and the banburying time is 8-12 min.

[0023] Preferably, the initiator in step (4) is dicumyl peroxide.

[0024] Preferably, in step (5), the mass ratio of high-density polyethylene, modified high-density polyethylene, modified filler, antioxidant and lubricant is 100:3-7:1-3:0.3-0.5:0.1-0.3.

[0025] Preferably, the mixing temperature in step (5) is 180-200° C., and the mixing time is 6-9 min.

[0026] Preferably, the antioxidant in step (5) is antioxidant 168.

[0027] Preferably, the lubricant in step (5) is polyethylene wax.

[0028] A high-toughness polyethylene composite material prepared by adopting the preparation method of the high-toughness polyethylene composite material.

[0029] An application of the high-toughness polyethylene composite material in polyethylene plastic film.

[0030] (III) Beneficial technical effects

[0031] In the present invention, γ-glycidyloxypropyltrimethoxysilane is used to modify shell powder to obtain epoxidized shell powder, epoxy groups are introduced on the surface of shell powder, γ-aminopropyltriethoxysilane is used to modify carbon nanotubes, amino groups are introduced on carbon nanotubes to obtain amino carbon nanotubes, and epoxidized shell powder and amino carbon nanotubes undergo ring-opening reaction to obtain modified fillers. High-density polyethylene, maleic anhydride, and ethylene-vinyl acetate copolymer are polymerized under the action of an initiator, and ethylene-vinyl acetate copolymer and maleic anhydride are introduced into high-density polyethylene to obtain modified high-density polyethylene. High-density polyethylene, modified high-density polyethylene, modified fillers, antioxidants, and lubricants are mixed to obtain high-toughness polyethylene composite materials.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) In the present invention, high-density polyethylene is used as the main matrix of the composite material, has excellent mechanical properties, a tight molecular chain structure, and has high strength and toughness. Shell powder is used as an inorganic filler, which is cheap and easy to obtain, and can significantly improve the tensile strength and impact strength of polyethylene. At the same time, shell powder has high thermal stability and can improve the heat resistance of the composite material. Carbon nanotubes have extremely high strength and toughness. When added to the polyethylene matrix, they can play the role of nano-reinforced phase, significantly improving the mechanical properties and toughness of the composite material. At the same time, carbon nanotubes have extremely high thermal stability, which can further improve the heat resistance and thermal stability of the composite material.

[0034] (2) The maleic anhydride introduced into the modified high-density polyethylene of the present invention can increase the polarity of polyethylene, making it more compatible with other polar materials. The flexible segments in the ethylene-vinyl acetate copolymer can improve the toughness and impact resistance of the material. Through copolymerization, these functional groups and segments are uniformly introduced into the molecular chain of the high-density polyethylene, thereby achieving the modification of its performance. The non-polar ethylene segments in the ethylene-vinyl acetate copolymer have good compatibility with polyethylene, and the polar vinyl acetate segments have good interface bonding with the modified filler. The anhydride groups in the modified high-density polyethylene can form hydrogen bonds and interaction forces with the active matrix in the modified filler, further improving the compatibility and dispersibility between the matrixes, and the toughness of the composite material is improved.

[0035] (3) The hydroxyl groups and unreacted active groups introduced after the epoxy ring opening in the modified filler of the present invention can react chemically or physically entangle with the polyethylene molecular chain, thereby improving the interfacial bonding force between the filler and the matrix, playing a role of strengthening and toughening in the composite material, and also reducing the cost of the composite material. After the ring opening reaction of the epoxidized shell powder and the amino carbon nanotubes, the agglomeration of the shell powder and the carbon nanotubes is effectively avoided by the chemical connection method, and they can be evenly dispersed in the matrix. Furthermore, the two work synergistically and have excellent dispersibility and stability. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] A method for preparing a high-toughness polyethylene composite material comprises the following steps:

[0039] (1) mixing liquid paraffin and γ-glycidyloxypropyl trimethoxysilane evenly, adding shell powder, wherein the mass ratio of liquid paraffin, γ-glycidyloxypropyl trimethoxysilane and shell powder is 1500:35:100, heating and stirring, reacting, the reaction temperature is 105° C., the reaction time is 2 h, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 h, grinding evenly, and obtaining epoxidized shell powder;

[0040] (2) ultrasonically dispersing the hydroxylated multi-walled carbon nanotubes into deionized water, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the hydroxylated multi-walled carbon nanotubes, deionized water, and γ-aminopropyltriethoxysilane is 100:4800:42, stirring and mixing, reacting at 25° C. for 30 hours, and after the reaction is completed, centrifuging, washing with anhydrous ethanol, and drying at 80° C. for 24 hours to obtain amino carbon nanotubes;

[0041] (3) Butyl acetate, epoxidized shell powder, and amino carbon nanotubes in a mass ratio of 2500:100:85 were mixed, heated, and reacted in a nitrogen atmosphere at a temperature of 80° C. for 8 h. After the reaction was completed, the mixture was rotary evaporated and dried at 80° C. for 12 h to obtain a modified filler;

[0042] (4) High-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator dicumyl peroxide are mixed uniformly in a mass ratio of 100:1:5:0.1, and kneaded in a Hake mixer. During the kneading process, the speed is 40 r / min, the kneading temperature is 160° C., and the kneading time is 12 min to obtain a modified high-density polyethylene;

[0043] (5) High-density polyethylene, modified high-density polyethylene, modified filler, antioxidant 168, and lubricant polyethylene wax are uniformly mixed in a mass ratio of 100:3:1:0.3:0.1, and kneaded in a double-roll open plastic mill at a mixing temperature of 180° C. for 9 minutes to obtain a high-toughness polyethylene composite material.

[0044] Example 2

[0045] A method for preparing a high-toughness polyethylene composite material comprises the following steps:

[0046] (1) mixing liquid paraffin and γ-glycidyloxypropyl trimethoxysilane evenly, adding shell powder, wherein the mass ratio of liquid paraffin, γ-glycidyloxypropyl trimethoxysilane and shell powder is 1700:42:100, heating and stirring, reacting, the reaction temperature is 110° C., the reaction time is 1.5 h, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 h, grinding evenly, and obtaining epoxidized shell powder;

[0047] (2) ultrasonically dispersing the hydroxylated multi-walled carbon nanotubes into deionized water, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the hydroxylated multi-walled carbon nanotubes, deionized water, and γ-aminopropyltriethoxysilane is 100:5200:50, stirring and mixing, reacting at 30° C. for 26 hours, and after the reaction is completed, centrifuging, washing with anhydrous ethanol, and drying at 80° C. for 24 hours to obtain amino carbon nanotubes;

[0048] (3) mixing butyl acetate, epoxidized shell powder, and amino carbon nanotubes in a mass ratio of 3000:100:110, heating and reacting in a nitrogen atmosphere at a temperature of 90° C. for 6 h. After the reaction, rotary evaporation and drying at 80° C. for 12 h were performed to obtain a modified filler;

[0049] (4) High-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator dicumyl peroxide are mixed uniformly in a mass ratio of 100:1.5:15:0.15, and kneaded in a Hake mixer. During the kneading process, the speed is 50 r / min, the kneading temperature is 170° C., and the kneading time is 10 min to obtain a modified high-density polyethylene;

[0050] (5) High-density polyethylene, modified high-density polyethylene, modified filler, antioxidant 168, and lubricant polyethylene wax are uniformly mixed in a mass ratio of 100:4:1.5:0.4:0.2, and kneaded in a double-roll open plastic mill at a mixing temperature of 190° C. for 8 min, and discharged to obtain a high-toughness polyethylene composite material.

[0051] Example 3

[0052] A method for preparing a high-toughness polyethylene composite material comprises the following steps:

[0053] (1) High-density polyethylene, modified high-density polyethylene, modified filler, antioxidant 168, and lubricant polyethylene wax are uniformly mixed in a mass ratio of 100:6:2.5:0.4:0.2, and kneaded in a double-roll open plastic mill at a mixing temperature of 190° C. for 8 min, and discharged to obtain a high-toughness polyethylene composite material.

[0054] The preparation method of the modified filler and the modified high-density polyethylene is the same as the preparation method of the modified filler and the modified high-density polyethylene in Example 2.

[0055] Example 4

[0056] A method for preparing a high-toughness polyethylene composite material comprises the following steps:

[0057] (1) mixing liquid paraffin and γ-glycidyloxypropyl trimethoxysilane evenly, adding shell powder, wherein the mass ratio of liquid paraffin, γ-glycidyloxypropyl trimethoxysilane and shell powder is 1800:50:100, heating and stirring, reacting, the reaction temperature is 115° C., the reaction time is 1 hour, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 hours, grinding evenly, and obtaining epoxidized shell powder;

[0058] (2) ultrasonically dispersing the hydroxylated multi-walled carbon nanotubes into deionized water, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the hydroxylated multi-walled carbon nanotubes, deionized water, and γ-aminopropyltriethoxysilane is 100:5500:60, stirring and mixing, reacting at 35° C. for 24 hours, and after the reaction is completed, centrifuging, washing with anhydrous ethanol, and drying at 80° C. for 24 hours to obtain amino carbon nanotubes;

[0059] (3) Butyl acetate, epoxidized shell powder, and amino carbon nanotubes in a mass ratio of 3500:100:120 were mixed, heated, and reacted in a nitrogen atmosphere at a temperature of 95° C. for 5 h. After the reaction was completed, the mixture was rotary evaporated and dried at 80° C. for 12 h to obtain a modified filler;

[0060] (4) High-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator dicumyl peroxide are mixed uniformly in a mass ratio of 100:2:20:0.2, and kneaded in a Hake mixer. During the kneading process, the speed is 60 r / min, the kneading temperature is 180° C., and the kneading time is 8 min to obtain a modified high-density polyethylene;

[0061] (5) High-density polyethylene, modified high-density polyethylene, modified filler, antioxidant 168, and lubricant polyethylene wax are uniformly mixed in a mass ratio of 100:7:3:0.5:0.3, and kneaded in a double-roll open plastic mill at a mixing temperature of 200° C. for 6 min, and discharged to obtain a high-toughness polyethylene composite material.

[0062] Comparative Example 1

[0063] A method for preparing a polyethylene composite material comprises the following steps:

[0064] (1) mixing liquid paraffin and γ-glycidyloxypropyl trimethoxysilane evenly, adding shell powder, wherein the mass ratio of liquid paraffin, γ-glycidyloxypropyl trimethoxysilane and shell powder is 1700:42:100, heating and stirring, reacting, the reaction temperature is 110° C., the reaction time is 1.5 h, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 h, grinding evenly, and obtaining epoxidized shell powder;

[0065] (2) ultrasonically dispersing the hydroxylated multi-walled carbon nanotubes into deionized water, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the hydroxylated multi-walled carbon nanotubes, deionized water, and γ-aminopropyltriethoxysilane is 100:5200:50, stirring and mixing, reacting at 30° C. for 26 hours, and after the reaction is completed, centrifuging, washing with anhydrous ethanol, and drying at 80° C. for 24 hours to obtain amino carbon nanotubes;

[0066] (3) High-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator dicumyl peroxide are mixed uniformly in a mass ratio of 100:1.5:15:0.15, and kneaded in a Hake mixer. During the kneading process, the speed is 50 r / min, the kneading temperature is 170° C., and the kneading time is 10 min to obtain a modified high-density polyethylene;

[0067] (4) High-density polyethylene, modified high-density polyethylene, epoxidized shell powder, amino carbon nanotubes, antioxidant 168, and lubricant polyethylene wax are mixed evenly in a mass ratio of 100:6:1.2:1.3:0.4:0.2, and kneaded in a double-roll open plastic mill at a mixing temperature of 190° C. for 8 min, and discharged to obtain a polyethylene composite material.

[0068] Comparative Example 2

[0069] A method for preparing a polyethylene composite material comprises the following steps:

[0070] (1) mixing liquid paraffin and γ-glycidyloxypropyl trimethoxysilane evenly, adding shell powder, wherein the mass ratio of liquid paraffin, γ-glycidyloxypropyl trimethoxysilane and shell powder is 1700:42:100, heating and stirring, reacting, the reaction temperature is 110° C., the reaction time is 1.5 h, after the reaction is completed, filtering, washing with anhydrous ethanol, drying at 80° C. for 24 h, grinding evenly, and obtaining epoxidized shell powder;

[0071] (2) ultrasonically dispersing the hydroxylated multi-walled carbon nanotubes into deionized water, and after uniform dispersion, adding γ-aminopropyltriethoxysilane, wherein the mass ratio of the hydroxylated multi-walled carbon nanotubes, deionized water, and γ-aminopropyltriethoxysilane is 100:5200:50, stirring and mixing, reacting at 30° C. for 26 hours, and after the reaction is completed, centrifuging, washing with anhydrous ethanol, and drying at 80° C. for 24 hours to obtain amino carbon nanotubes;

[0072] (3) mixing butyl acetate, epoxidized shell powder, and amino carbon nanotubes in a mass ratio of 3000:100:110, heating and reacting in a nitrogen atmosphere at a temperature of 90° C. for 6 h. After the reaction, rotary evaporation and drying at 80° C. for 12 h were performed to obtain a modified filler;

[0073] (4) High-density polyethylene, ethylene-vinyl acetate copolymer, modified filler, antioxidant 168, and lubricant polyethylene wax are uniformly mixed in a mass ratio of 100:6:2.5:0.4:0.2, and kneaded in a double-roll open plastic mill at a mixing temperature of 190° C. for 8 min, and discharged to obtain a high-toughness polyethylene composite material.

[0074] Comparative Example 3

[0075] A method for preparing a polyethylene composite material comprises the following steps:

[0076] (1) High-density polyethylene, ethylene-vinyl acetate copolymer, shell powder, hydroxylated multi-walled carbon nanotubes, antioxidant 168, and lubricant polyethylene wax in a mass ratio of 100:6:1.2:1.3:0.4:0.2 were uniformly mixed, and kneaded in a double-roll open plastic mill at a mixing temperature of 190° C. for a mixing time of 8 min, and the material was discharged to obtain a polyethylene composite material.

[0077] The shell powder used in the embodiments and comparative examples of the present invention was purchased from Hunan Changde Shell Powder Production Co., Ltd., with a particle size of 7 μm; hydroxylated multi-walled carbon nanotubes were purchased from Shanghai McLean Technology Biochemical Co., Ltd., with a particle size of 10-20 nm; high-density polyethylene (HDPE): MI = 3.0 g / 10 min; ethylene-vinyl acetate copolymer (EVA): VA% = 28%, MI = 3.5 g / 10 min; all raw materials used without other explanations are commercially available raw materials.

[0078] Corresponding tests were performed on the polyethylene composite materials prepared in Examples 1-4 and Comparative Examples 1-3. The test specimens were injection molded using a Haake micro injection molding apparatus (MiniJetⅡ). The test methods and test results are as follows:

[0079] (1) Tensile property test: The specimens were cut into dumbbell-shaped specimens of 8 cm × 1.5 cm × 1 cm. The test standard was based on ISO527-2-5A. The specimens were subjected to tensile property tests using a CMT4204 electronic universal testing machine. Each group was tested five times and the average value was taken.

[0080] (2) Impact performance test: The specimens were cut into rectangular strips of 8 cm × 1.5 cm × 1 cm. The test standard was based on ISO179. The strips were tested for impact performance using a PTM7251-C pendulum impact tester. Each group was tested five times and the average value was taken.

[0081] The above test results are shown in Table 1:

[0082] Table 1

[0083]

[0084] According to the test results in Table 1, it can be seen that the corresponding polyethylene composite materials in Examples 1-4 have excellent mechanical properties, high impact strength and good toughness. In Comparative Example 3, shell powder and carbon nanotubes were not modified, and ethylene-vinyl acetate copolymer was directly added, the dispersibility and compatibility between the raw materials were poor, and the comprehensive performance was greatly reduced.

[0085] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing a high-toughness polyethylene composite material, characterized in that: The steps include: Step (1), mixing liquid paraffin and γ-glycidyloxypropyltrimethoxysilane evenly, adding shell powder, heating and stirring, reacting, after the reaction is completed, filtering, washing, drying at 80° C. for 24 hours, and grinding evenly to obtain epoxidized shell powder; Step (2), ultrasonically dispersing the carbon nanotubes into deionized water, adding γ-aminopropyltriethoxysilane after the dispersion is uniform, stirring and mixing, reacting, centrifuging, washing, and drying at 80° C. for 24 h to obtain amino carbon nanotubes; Step (3), mixing butyl acetate, epoxidized shell powder and amino carbon nanotubes, heating and reacting in a nitrogen atmosphere, and after the reaction, rotary evaporating and drying at 80° C. for 12 h to obtain a modified filler; Step (4), mixing high-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator uniformly, and mixing in a Hake mixer to obtain modified high-density polyethylene; Step (5), uniformly mixing high-density polyethylene, modified high-density polyethylene, modified filler, antioxidant, and lubricant, kneading in a double-roll open plastic mill, and discharging to obtain a high-toughness polyethylene composite material.

2. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (1), the mass ratio of liquid paraffin, γ-glycidyloxypropyltrimethoxysilane and shell powder is 1500-1800:35-50:100, the reaction temperature is 105-115° C., and the reaction time is 1-2 h.

3. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (2), the mass ratio of carbon nanotubes, deionized water and γ-aminopropyltriethoxysilane is 100:4800-5500:42-60, the reaction temperature is 25-35° C., and the reaction time is 24-30 hours.

4. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (3), the mass ratio of butyl acetate, epoxidized shell powder and amino carbon nanotubes is 2500-3500:100:85-120, the reaction temperature is 80-95°C, and the reaction time is 5-8h.

5. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (4), the mass ratio of high-density polyethylene, maleic anhydride, ethylene-vinyl acetate copolymer and initiator is 100:1-2:5-20:0.1-0.

2. During the banburying process, the rotation speed is 40-60r / min, the banburying temperature is 160-180°C, and the banburying time is 8-12min.

6. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (5), the mass ratio of high-density polyethylene, modified high-density polyethylene, modified filler, antioxidant and lubricant is 100:3-7:1-3:0.3-0.5:0.1-0.

3.

7. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: The mixing temperature in step (5) is 180-200° C., and the mixing time is 6-9 minutes.

8. The method for preparing a high-toughness polyethylene composite material according to claim 1, characterized in that: In the step (5), the antioxidant is antioxidant 168 and the lubricant is polyethylene wax.

9. A high-toughness polyethylene composite material prepared by the method for preparing a high-toughness polyethylene composite material according to any one of claims 1 to 8.

10. Use of the high-toughness polyethylene composite material as claimed in claim 9 in polyethylene plastic film.

Citation Information

Patent Citations

  • PPR / EVOH / POE (Pentatricopeptide Repeats / Ethylene-Vinyl Alcohol / Polyolefin Elastomer) blending high-impact barrier pipe and manufacturing method thereof

    CN102002191A

  • Polyethylene film with high mechanical strength and good wear resistance and preparation method thereof

    CN110452437A